Factors of winning and losing of an election case study: N.9 Padungan & N14 Asajaya Sarawak State Election 2011 / Abang Zulkernain Abang Yusuf & Paul Racha - Abang Yusuf, Abang Zulkernain; Racha, Paul (2011)
Predominantly, politics has an expressive landscape and elections are the main architects of these landscape. In the Malaysian context, its landscape has been shaped by elections dated since 27 July 1955 and Merdeka in 1957. Despite enjoying regular elections and political stability, Zakaria (2000) highlighted a turnover in the Malaysian politics and the election results was heralded as a barometer of the electorate’s choice and an expression of happiness or dissatisfaction with the government in power and its adversaries. Crouch and Harold (1993) labeled the Malaysian participatory political system as semi democratic as the requirement for a fully fledge democracy is of three essential conditions which are extensive political competition, high level of political participation and guaranteed civil and political liberties. This is further postulated by Jesudason (1996) which has described Malaysia as a syncretic state, which operates at a multidimensional level, mixing coercive elements with electoral and democratic procedures and propagating religion in society as it pursues secular economic goals, engaging in ethnic mobilization while inculcating national feelings. Malaysia’s bicameral parliament consists of the Senate and the House of Representative. 29 senators of the Dewan Negara are appointed by the State assemblies, while the King appoints the remaining 40 senators. The federal parliament presently holds 193 member constituencies with plurality voting, Federal elections are held at intervals no longer than five years. Each of the states has a unicameral State Legislative Assembly, whose members are elected at the same time and in the same manner to the federal elections. The “First Past the Post” (FPTP) system in Malaysia has led to a broad governing coalition (BN, Barisan Nasional, “National Front”) of 13 parties representing various ethnicities. Likewise, the system presents an incentive to the opposition parties to follow the example of the ruling coalition and merge in a comparable coalition oppositionist.